Helichrysum italicum (Roth) G. Don subsp. italicum from Herzegovina volatile composition, variations during seasons, total polyphenols, acetylcho-linesterase inhibition and antioxidant activity - Talić, Stanislava; Odak, Ilijana; Bevanda Martinović, Anita; Crnjac, Nikolina; Paštar, Mate (2019)
The chemical composition of essential oils isolated from immortelle (Helicrysum italicum subsp. italicum) collected in Herzegovina during five different periods, was investigated by GC/MS analysis. The main compounds were a-pinene (15.7 %) and γ-curcumene (12.8 %), followed by 4,6,9-trimethyldec-8-en-3,5-dione (8.7 %), neryl acetate (6.9 %), limonene (6.4 %) and β-selinene (5.3 %). In total, 69 components were identified whose share changed over the vegetative cycle. Antioxidant activity of methanolic extracts of immortelle were determined according to DPPH (IC50 = 23–34 μg/mL) and FRAP (29 μg/mL is equivalent to 1.1‒2.2 mM Fe2+) methods. Acetylcholinesterase inhibitory potential, investigated by modified Ellman’s assay and determined as IC50 values, were 340–440 μg/mL for methanol extracts and 135 μg/mL for essential oil. Metanolic extracts showed strong antioxidant activity and potential to inhibit AChE. Essential oil possesses complex chemical composition, inhibition activity of AChE and weak antioxidant capacity.
Bibliografija: 42 jed.
Abstract.
Keywords: Smilje -- Helichrysum italicum -- Polifenoli -- Antioksidativno djelovanje